Influence of Organizational Climate Towards Polyglot Indonesia Members Intercultural Communication Skill Mediated by Self Motivation - Putra, Nararia Hutama; Sutarto, Joko; Yusuf, Amin (Universitas Negeri Semarang, 2021)
Polyglot Indonesia is a form of nonformal learning organization that concerns on developing the intercultural communication skill of its members. This study shows how the organization element (organizational climate) helps to develop intercultural communication skill of the members. The aim of this study is to analyze the influence of organizational climate mediated by self motivation towards intercultural communication skill of Polyglot Indonesia members. This study is categorized as ex-postfacto study with quantitative approach. The population of this study are 152 members of Polyglot Indonesia who have been joining the whatsapp group of Polyglot Indonesia All chapters and the sample that used in this study are 110 respondents. The data were collected through online questionnaire. The data analysis was using SPSS 21.0 Software. The results and conclusion of this study are, (1) t value regression of X variable towards Y is 2,122 and significance level is 0,036, which means there is a significant direct influence on organizational climate towards intercultural communication skill of Polyglot Indonesia members; (2) t value regression of X variable towards Z is 2,957 and significance level is 0,004, which means there is significant direct influence on organizational climate towards self motivation of Polyglot Indonesia members; (3) t value regression of X variable towards Y mediated by Z is 2,333 and significance level is 0,05, which means there is a significant indirect influence on organizational climate mediated by self motivation towards intercultural communication skill of Polyglot. Indonesia members. This study new finding shows that self motivation strengthened the impact of organization element in achieving organization goal as nonformal learning organization. The study benefit for the science development is to show a form of nonformal learning through learning organization and enhance the knowledge of the core value of nonformal learning itself.